Race and mortality risk after radiation therapy in men treated with or without androgen‐suppression therapy for favorable‐risk prostate cancer. Issue 23 (4th August 2016) - Kovtun, Konstantin A.; Chen, Ming‐Hui; Braccioforte, Michelle H.; Moran, Brian J.; D'Amico, Anthony V.
Abstract : BACKGROUND: African American (AA) men are more likely than non‐AA men to have a comorbid illness that could interact with androgen‐deprivation therapy (ADT) and shorten survival. This study assessed the impact that race had on the risk of all‐cause mortality (ACM) and other‐cause mortality (OCM) among men definitively treated for favorable‐risk prostate cancer (PC). METHODS: Between 1997 and 2013, 7252 men with low‐risk or favorable intermediate‐risk PC were treated with brachytherapy with neoadjuvant ADT (n = 1501) or without neoadjuvant ADT (n = 5751) for a 4‐month median duration. Cox and Fine‐Gray multivariate regressions were used to analyze whether the risk of ACM and OCM increased among AA men versus non‐AA men receiving ADT; adjustments were made for the age at brachytherapy, year of brachytherapy, cardiometabolic comorbidity status, risk group, and ADT treatment propensity score. RESULTS: After a median follow‐up of 8.04 years, 869 men (12.0%) died: 48 (5.52%) of PC and 821 (94.48%) of other causes. There was a significant association between AA race and an increased risk of both ACM (adjusted hazard ratio [AHR], 1.77; 95% confidence interval [CI], 1.06‐2.94; P = .028) and OCM (AHR, 1.86; 95% CI, 1.08‐3.19; P = .024) among AA men versus non‐AA men who received ADT but not among those who did not receive ADT (AHR for ACM, 1.33; 95% CI, 0.93‐1.91; P = .12; AHR for OCM, 1.39; 95% CI, 0.96‐2.02; P = .08). CONCLUSIONS: ADT use may shorten survival in AA men with favorable‐risk PC; therefore, its reservation for the treatment of higher risk PC, for which level 1 evidence supports its use, should be considered. Cancer 2016;122:3608‐14. © 2016 American Cancer Society . Abstract : In the setting of low‐risk or favorable intermediate‐risk prostate cancer, androgen‐deprivation therapy (ADT) is often used in the absence of level 1 evidence to reduce the size of the prostate to allow men with large prostates and/or pubic arch interference to become candidates for prostate brachytherapy. A study of 7252 men with low‐risk or favorable intermediate‐risk prostate cancer treated with brachytherapy with or without ADT has found that the use of ADT in this setting leads to worse all‐cause and other‐cause mortality among African American men after adjustments for the age at brachytherapy, year of brachytherapy, cardiometabolic comorbidity status, risk group, and ADT treatment propensity score. This provides evidence supporting the consideration of limiting ADT use to the treatment of higher risk prostate cancer in African American men, for which level 1 evidence supports its use.